A Cross-Sectional Study on Patient Safety Culture in a Tertiary Care Hospital in India - Bhaladhare, Roshan; Rishipathak, Parag (International Journal of Statistics in Medical Research, 2025)
Aim: The study was to assess the patient safety culture in a tertiary care hospital in India using the HSOPSC survey. It also sought to compare the findings with global data to identify strengths and areas for improvement in patient safety practices. Methods: This cross-sectional study used the Hospital Survey on Patient Safety Culture (HSOPSC) version 2.0 to assess patient safety culture at a tertiary care hospital in India. The survey was administered to healthcare professionals across various specialties, with responses analyzed using SPSS software. Comparative analysis was conducted with global data from the AHRQ database to evaluate differences in patient safety perceptions. Findings: Findings revealed that while the hospital performed well in areas like organizational learning and communication about errors, it scored lower in domains such as staffing, error reporting, and teamwork compared to global data. A significant portion of staff reported challenges with staffing levels and work pace. Error reporting was less frequent, with many staff members indicating underreporting of incidents. Teamwork and communication within multidisciplinary teams also showed room for improvement, especially in overcoming hierarchical barriers. These results emphasize the need for better staffing practices, a supportive reporting environment, and enhanced interprofessional collaboration. Conclusion: This study highlights the strengths and weaknesses in patient safety culture at a tertiary care hospital in India, with notable gaps in staffing, error reporting, and teamwork. Addressing these challenges through improved staffing levels, non-punitive reporting systems, and team-building initiatives could enhance patient safety. The findings suggest that fostering a supportive and open safety culture is essential for reducing medical errors. The study provides valuable insights for healthcare policymakers to implement targeted interventions for safer patient care in Indian hospitals.